PERANCANGAN SISTEM INFORMASI PENGREKRUTAN ANGGOTA BEM BERBASIS WEB DI INSTITUT BISNIS MUHAMMADIYAH BEKASI - KEZALDO KEZALDO; SONY ABRIANTORO (Jupiter: Journal of Computer & Information Technology, 2021)
The development of information technology today requires us to continue to adaptand develop. This has become an encouragement in an administration, namely theBekasi Muhammadiyah Business Institute to improve and develop and update anyvarious information to support a better service. Recruitment of BEM Members at theIBM Bekasi campus still uses the manual method, where the recruiting committee still uses leaflets. documents in recruiting Anggota BEM. The purpose of this research is to produce an information system application based on the recruitment website at IBM Bekasi which was previously still done manually into a system in the form of a website. The method that researchers use in this study is in the form of observation, interviews, analysis, as well as system design and development and system testing, system implementation